Code Mixing In the Film COCO - Ardianto, Farhan -; Zamruddin, Mardliya Pratiwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
This research analyzes the code mixing used in the film. This research aims to analyze the code-mixing type in this film, based on Imelda and Hector's character dialogue in this film. This film uses code-mixing to communicate with each other, and the setting of the place is in a small village in Spain. They used code mixing because of the cultural background in there. One branch of socio-linguistic science is code mixing; code mixing has a few types that must be known they are insertion, alternation, and congruent lexicalization. Each type has its own rules, and they are different with each type; in this thesis, there are two types of code mixing: insertion and congruent lexicalization are the two types in this thesis. The code mixing are found in the character dialogue in this film, where use English and Spanish language to communicate. There is 13 data total that divide into 11 insertion type and 2 congruents lexicalization type.